Spatiotemporal Transcriptomic Profiling Reveals the Dynamic Immunological Landscape of Alveolar Echinococcosis - Zhihua Ou; Li Li; Peidi Ren; Ting‐Ting Zhou; Fan He; Jialing Chen; Huimin Cai; Xiumin Han; Yao‐Dong Wu; Jiandong Li; Xiu‐Rong Li; Qiming Tan; et al. (Advanced Science)
Abstract Alveolar echinococcosis (AE) is caused by the chronic infection of E. multilocularis, whose tumor‐like growth can lead to high fatality if improperly treated. The early diagnosis of infection and the treatment of advanced AE remain challenging. Herein, bulk RNA‐seq, scRNA‐seq, and spatial transcriptomics technologies are integrated, to reveal the host immune response mechanism against E. multilocularis both spatially and chronologically, collecting mouse liver samples at multiple timepoints up to 15 months post infection. These results unveil an unprecedented high‐resolution spatial atlas of the E. multilocularis infection foci and the functional roles of neutrophils, Spp1+ macrophages, and fibroblasts during disease progression. The heterogeneity of neutrophil and macrophage subpopulations are critical in both parasite‐killing and the occurrence of immunosuppression during AE progression. These findings indicate the transition of parasite control strategy from “active killing” to “negative segregation” by the host, providing instructive insights into the treatment strategy for echinococcosis.